ANALISIS KESULITAN BELAJAR PEMBELAJARAN IPS BAGI SISWA DISEKOLAH MTS ARAFAH BINJAI - Irfan Azhari Ritonga; Sakti Ritonga (Prodi Tadris Ilmu Pengetahuan Sosial FITK UIN Sumatera Utara Medan, 2026)
Analysis of Students’Learning Difficulties in Map Material Learning at MTs Arafah Binjai his study aims to analyze the factors causing learning difficulties for students at MTs Arafah Binjai, specifically focusing on map material within the Geography/Social Studies curriculum. Map reading and interpretation are often considered abstract and complex tasks for junior high school students due to the spatial cognition required. The research method used is a descriptive qualitative approach. Data were collected through diagnostic tests, observations, and interviews with both students and teachers at MTs Arafah Binjai. The findings indicate that MTs arafah Binjai the fingds indicate that studens elerning diffculties Stem froom booth internal and external factory factory internal factory Include a lacke of spatial awwarenes andy low interesct geofraphy map Include innaduquate learning media such as loke cloup maap traditional Teaching methodess in scocial studie ips the resulty of the material to.